Entrepreneurial intentions of Colombian business students: Planned behaviour, leadership skills and social capital (2017)
Purpose: The purpose of this paper is to reconceptualize the theory of planned behaviour (TPB) in the light of social cognitive theory to investigate the role of social capital, specifically the leadership skill as a social capital generating influence in the formation of entrepreneurial intentions. Design/methodology/approach: A new conceptualization of TPB is proposed to allow the impact of bonding and bridging cognitive social capital to be mediated by TPB constructs of perceived desirability and feasibility of entrepreneurship. Hypotheses are developed related to leadership skills, family background and social norms as external and internal indicators of social capital, and tested on primary data from 322 student respondents in a Colombian business school. Findings: Leadership skills, indicative of bridging cognitive social capital, are found to be strongly and significantly associated with entrepreneurial intentions through the mediating role of the core TPB constructs. Evidence for the role of bonding social capital through measures of the social acceptability of entrepreneurship and family background is mixed, and in the case of family background no indirect association with intentions is found. Research limitations/implications: Although the Latin American context would suggest significant population variation in personal and background resource, there is relatively little variation across this sample, particularly in terms of family background. Thus, rates of graduate entrepreneurship may relate more closely to constraints acting on entry into higher education than on other background characteristics, and therefore future work in similar contexts ought to be conducted across a wider socio-economic sample. Practical implications: Opportunities to develop and enhance student perception of leadership ability through either education or experience might improve levels of graduate entrepreneurship, alongside traditional activities to raise self-efficacy and perceived salience of entrepreneurship. Originality/value: Student leadership skills have rarely been addressed in the context of entrepreneurship development. This paper highlights the relevance of this in a developing economy context. © 2017, © Emerald Publishing Limited.